2007
DOI: 10.1002/bmc.771
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of N‐acetyl and N‐glycolylneuraminic acids in secreted and cell‐associated glycoconjugates by two human osteosarcoma cell lines

Abstract: N-acetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc) are the dominant sialic acids (Sia) in mammals usually found in the non-reducing terminal of oligosaccharide side chains in glycoproteins and glycolipids. Their expression and distribution pattern have been correlated both with the malignant phenotype and tumor grade of human cancers. The aim of the present study was to determine by reversed-phase HPLC method the amounts of Neu5Ac and Neu5Gc as well as their distribution among the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…The most abundant type was Neu5Ac in both cell-associated and secreted forms followed by Neu5Gc. This data shows different results when compared with the findings in the osteosarcoma cell line, MG-63, which was isolated from patients with different nationality with altered chromosomes 15 . Trace amounts of KDN was also detectable in both osteosarcomas and osteoblasts.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The most abundant type was Neu5Ac in both cell-associated and secreted forms followed by Neu5Gc. This data shows different results when compared with the findings in the osteosarcoma cell line, MG-63, which was isolated from patients with different nationality with altered chromosomes 15 . Trace amounts of KDN was also detectable in both osteosarcomas and osteoblasts.…”
Section: Discussioncontrasting
confidence: 65%
“…The main cell-associated Sia found in MG-63 was Neu5Gc, whereas that from the secreted form was Neu5Ac. This indicated that the human osteosarcoma cells expressed both forms of Sia-containing glycoconjugates and the differences in the amounts of each of the two major Sia types and their distribution may be related to the morphology and/or metastatic of osteosarcoma 15 . Another studies of Sia level in the serum reported that the amount of Sia in the serum of osteosarcoma patients was higher than in the control group, but did not differ from those of other bone-forming groups 16 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Both cell lines are of comparable size, yet in vivo MG-63 cells have a higher metastatic potential. [10] In addition, MG-63 cells have a higher proliferation rate (shorter cell cycle time). [11] When grown on microstructured surfaces, both MG-63 and SaOs-2 showed a deformation of their nuclei and their cytoskeleton, visible in the fluorescence microscopy image (Fig.…”
mentioning
confidence: 99%
“…In the present study we used human osteosarcoma Mg-63 cells (characterized by a high metastatic potential in vivo) and Soas-2 cells (characterized by a low metastatic potential) (21,22). These two cell lines were purchased from ATCC (LGC Promochem, Wesel, Germany), and were cultured in DMEM medium (Sigma, USA) supplemented with 10% FBS (Amresco, USA) and 1% penicillin/ streptomycin.…”
Section: Methodsmentioning
confidence: 99%